Keep calm and think uniportal - Gonzalez-Rivas, Diego; Jiang, Gening; Zhu, Yuming (Video-Assisted Thoracic Surgery; Vol 1 (September 2016): Video-Assisted Thoracic Surgery, 2016)
After many years of no evolution in our specialty, momentum is again with us, thanks to the explosion of minimally invasive techniques making our specialty more interesting than ever. The future offers many changes for thoracic surgery, and the forces in play are complex and myriad. The modern technology and recent innovative techniques make this an incredibly exciting time for our specialty.